2016
DOI: 10.1007/s12105-016-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Central Xanthoma of the Jaw Bones: A Benign Tumor

Abstract: Extragnathic xanthomas are seen in the bones or as soft tissue masses. They are often associated with hyperlipidemia and are considered as reactive or metabolic lesions. Only 19 cases of xanthomas of the jaws have been reported so far in the English literature. A total of ten cases of central xanthoma of the jaw bones were identified from the Oral and Maxillofacial Pathology biopsy services of the University of Washington and the Tufts University School of Dental Medicine, between the years 2000-2016. The demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 17 publications
4
48
0
1
Order By: Relevance
“…Glycaemia levels were reported in five studies and lipidemia levels in 12, being within normal limits in all cases. Only one study demonstrated a case of IOX of the jaws with hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Glycaemia levels were reported in five studies and lipidemia levels in 12, being within normal limits in all cases. Only one study demonstrated a case of IOX of the jaws with hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 77%
“…After the elimination of 192 duplicates, the parameters for inclusion and exclusion were applied to 442 references. A total of 16 articles reporting 31 cases of IOX of the jaws were selected . The studies included in the present literature review were case reports or case series.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compression of neurological structures may result in symptoms – as found in cases of intracranial xanthomas – but the lesion is otherwise considered asymptomatic. There are three reported cases of a maxillary intraosseous xanthoma within the literature and several cases of mandibular involvement, none of which report recurrence (see Table ). No malignant transformation of intraosseous xanthomas has been reported.…”
Section: Introductionmentioning
confidence: 99%